PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT OSI ELECTRONICS - Nurhelivia, Nurhelivia; Wangdara, Yvonne (SCIENTIA JOURNAL, 2020)
A company needs have good management in order to be able to compete in the business world. Good performance would help to maintain the quality and quantity to accomplish to maximum capacity, as well as optimisation. This research was conducted to analyse the impact of training and work motivation on employee performance at PT Osi Electronics. The method used in this study is quantitative research. The population in this study were employees of PT Osi Electronics in the wire harness department with 150 people or respondents. The sample technique used is saturated sample and with the help of SPSS Version 26. Findings of this research are as follows; training in partial has a significant effect on employee performance with table T value 2.279 < T table 1.976 and work motivation in partial effect significantly towards employee performance with T table value 6,697 > t table 1.976. Training and work motivation simultaneously effect on employee performance value 27.841 > F table 3.06.Keywords : Training, work motivation, employee performance